Prevention of Child Maltreatment - Lane, Wendy Gwirtzman (2014)
Pediatricians and other health care providers can play a number of important roles in the prevention of child maltreatment. As part of routine patient care, pediatricians can provide anticipatory guidance for effective discipline and parent-child communication, screen for maltreatment risk factors, and refer parents and families to effective community-based programs. This article will help pediatricians incorporate child abuse prevention into their practice. Resources for systematizing anticipatory guidance and child maltreatment risk factor screening will be described. The modalities and strengths and weaknesses of community-based prevention programs will be discussed, and providers will be given tools to identify the effectiveness of available community-based programs. At a broader level, the article will describe ways that pediatricians can advocate at the local, state, and national level for policies and programs that support families and children.